Manajemen Sekolah Terkait Analisis Pendekatan Hubungan Manusia terhadap Partisipasi Guru Pendidikan dalam Pengambilan Keputusan - Puja Devi Sri Raso Tampubolon (STKIP PGRI SITUBONDO, 2023)
Decision making by the principal is part of school management. The goals and even the school's vision and mission are part of a decision that is determined to be the hallmark of each school. The goals in every school are definitely the main focus that must be achieved by the school organization. It is not uncommon to find problems due to low teacher participation in decision making on teacher performance results. Low teacher performance will result in a low level of achievement of goals within the school itself. For this reason, it is especially important for school principals to use a human relations approach to build good relationships with teachers. The human relations approach describes how managers communicate with their employees. The purpose of this study is for school principals to improve relationships with teachers with a human relations approach. The research method used is qualitative research with literature study. The result of this study is to explain the theory of the human approach, the notion of decision making, and the human relations approach included in the Bible with the story of the Tower of Babel.